Evolution between forestry education and timber education: Definitions, formations, chronologies and perspectives (Research, Society and Development, 2021)
The first forestry schools were created in the Western Europe in the mid-eighteenth Century. In the late of 19th Century, Forest Education was structured to intervene in forestry ecosystems and ensure the sustainable management of their resources. Thus, forestry chain advanced in the quest for higher value and quality solutions. In the early of 20th Century, Timber Education was designed to approach the wood and its processing. Then, this paper aimed to examine, in the global and Brazilian scenarios, Forest Education and Timber Education to understand their features, chronologies and perspectives. Broad consultations in the websites of universities and scientific literature were carried out to ensure the necessary information to support discussions. Forest and Timber Education undergraduate courses have been titled by different designations, where generalist nomenclatures are frequent in the forestry areas and more specific names are common in the wood fields. The Forestry Education initiated in Europe and spread across the world over two centuries, arising in Brazil in the middle of the 20th Century. From modern industry technologies, the Timber Education was developed in the Northern Hemisphere, and it spread globally over a century until its insertion in Brazil at the end of the 20th Century. A student decline has been globally observed in these careers, reasons why new stimuli and policies are required by a society eager for sustainable bioproducts and genuinely concerned about environmental issues.